INFLUENCE OF NANOPARTICLES OF CuO ON THE STABILITY AND CONDUCTIVITY OF BLM - Torosyan, A.L.; Ananyan, G.V.; Arakelyan, V.B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
This study aims to provide arguments for an increase in the stability of bilayer lipid membranes (BLM) in an electrical field in presence of CuO nanoparticles. Moreover, the sustainability of BLM becomes more stable with increasing of nanoparticles concentration. It is shown that an increase in the stability of BLM in an electrical field is mainly due to an increase in the coefficient of linear tension of the edge of a pore, which is forming in BLM. It is shown as well, that the presence of nanoparticles of CuO in the solution surrounding BLM leads to a decrease in the conductivity of the BLM.